2023
DOI: 10.1111/1471-0528.17380
|View full text |Cite
|
Sign up to set email alerts
|

Maternal comorbidity and adverse perinatal outcomes in survivors of adolescent and young adult cancer: A cohort study

Abstract: Objective To evaluate risks of preterm birth (PTB) and severe maternal morbidity (SMM) in female survivors of adolescent and young adult cancer and assess maternal comorbidity as a potential mechanism. To determine whether associations differ by use of assisted reproductive technology (ART). Design Retrospective cohort. Setting Commercially insured females in the USA. Sample Females with live births from 2000–2019 within a de‐identified US administrative health claims data set. Methods Log‐binomial regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…US-based studies are fewer in number but have often had similar findings. A recent study of commercially insured women from across the United States reported a slightly but significantly higher risk of preterm delivery among births to AYA cancer survivors (N = 2654) compared to births to women without cancer (RR = 1.19; 95% CI: 1.06 to 1.34) ( 15 ). Similarly, in our prior analyses using statewide birth certificate and cancer registry data in North Carolina, births to women diagnosed with AYA cancer before the start of pregnancy were 1.23 (95% CI: 1.07 to 1.43) and 1.36 (95% CI: 1.16 to 1.59) times as likely to be preterm and LBW, respectively, as births to cancer-free women ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…US-based studies are fewer in number but have often had similar findings. A recent study of commercially insured women from across the United States reported a slightly but significantly higher risk of preterm delivery among births to AYA cancer survivors (N = 2654) compared to births to women without cancer (RR = 1.19; 95% CI: 1.06 to 1.34) ( 15 ). Similarly, in our prior analyses using statewide birth certificate and cancer registry data in North Carolina, births to women diagnosed with AYA cancer before the start of pregnancy were 1.23 (95% CI: 1.07 to 1.43) and 1.36 (95% CI: 1.16 to 1.59) times as likely to be preterm and LBW, respectively, as births to cancer-free women ( 16 ).…”
Section: Discussionmentioning
confidence: 99%